NILAI KETAKTERATURAN TOTAL SISI DARI GRAF SEGITIGA BERMUDA - Anjelia, Novalita; Slamin, S; Dafik, D (Kadikma, 2014)
Abstract.For a simple graph G, a labelling λ∶V(G)∪E(G)→ {1,2,…,k} is called an edge irregular total k-labelling of G if for any two different edges e and f of G there is, wt(e)≠wt(f). The total edge irregularity strength denoted by tes G is the smallest positive integer k for which G has an edge irregular total k-labelling. In this paper, we consider the total edge irregularity strength of Bermuda Triangle graph and the union isomorphic and non isomorphic Bermuda Triangle graph. We show that tes(〖Btr〗_(n,4) )= ⌈(30n+17)/3⌉, for n≥1, tes(〖sBtr〗_(n,4) )=⌈(s(30n+15)+ 2)/3⌉, for n≥1 and s≥2, and tes(〖Btr〗_(n,4)∪〖Btr〗_(m,4) )=⌈((30n+15)+ (30m+15)+ 2)/3⌉, for 1≤n≤m. Keywords:Edge irregular total labelling, Irregularity strength, Total edge irregularity strength, Bermuda Triangle graph.